Is it safe to use ceramic on polyethylene bearings in revision hip arthroplasty for ceramic fracture? - Christopher Gunn; Vivek Thakker; Sophie Williams; Timothy N Board; Henry Wynn-Jones; Jonathan Barrow (Bone & Joint Open)
Aims: Ceramic bearing fracture is a rare complication following implantation using modern ceramic bearing materials. The ideal revision bearing option in such cases is debated. We aimed to investigate the safety of a hard on soft bearing following ceramic fracture in total hip arthroplasty. Methods: Data on all patients undergoing revision following ceramic fracture between January 2016 and January 2019 were collected retrospectively. Templating software was used to determine linear wear between the first post-revision radiograph and latest available follow-up. Univariate analysis was used to examine patient demographics and the wear rates of the polyethylene components. The intra- and inter-rater reliability of wear measurements was calculated. Additionally, in vitro testing was undertaken to assess the effects on bearing surfaces of residual ceramic particles. Results: A total of 12 patients underwent revision for ceramic fracture in the study period. The mean age at revision was 62 years (54 to 72). There were six liner and six head fractures revised to delta ceramic heads and cross-linked polyethylene acetabular components. At mean follow-up of 3.8 years (0.5 to 6.1), median 4.4 years (IQR 2.0 to 5.1), linear wear rate was calculated at 0.08 mm/year (SD 0.06). Both intra- and inter-rater reliability was excellent with intraclass correlation coefficient (ICC) scores of 0.99 at all timepoints. In vitro testing showed an increase in head roughness in metal on polyethylene bearings after ceramic particles were embedded, but no increase in ceramic on polyethylene (CoP) or ceramic on ceramic bearings. Conclusion: Revision to CoP bearings following ceramic fracture does not cause early catastrophic wear at early follow-up, aligning with the in vitro study observations. It appears safe to use this hard on soft bearing combination, given that wear rates are comparable to what is expected in a primary hip arthroplasty setting. Longer follow-up is required to establish if this trend persists. Cite this article: Bone Jt Open 2025;6(6):700–706.